Analisis Kecepatan Rata-Rata Lalu Lintas Di Ruas Jalan Pilau Akibat Kendaraan Berbelok - Nirwana Puspasari (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Often we encounter several obstacles that cause traffic concentration at several points on a road segment which causes traffic movement to slow down and even stop. Concentration of traffic flow occurs at intersection points, such as one at the Pilau-Keruing intersection, where traffic moving on the Pilau road is forced to slow down when the traffic flow from Keruing road turns right to cut the flow. Therefore, it is very important to know the effect of turning movement on the smooth flow of traffic. Data collection was carried out by sending several surveyors to the field to obtain secondary and primary data. Furthermore, the analysis of road performance using the 1997 Indonesian Road Capacity Manual. The average space speed obtained from the graph of the relationship between DS and vlv is vlv=28 km/hour. The average speed from the results of the speed survey on the road section gives a value of vlv = 29.6 km / h with conditions without any obstacles to the flow of turning from the Keruing road to the Pilau road, and vlv = 25.6 km / h with the presence of turning current obstacles . There was a decrease in average travel time of 5.9 seconds, with a decrease in traffic speed of 4 km/hour due to the influence of vehicles turning from Keruing road to Jati road.